Cascade screening for glaucoma in high-risk family members of African-Caribbean glaucoma patients in an urban population in London. Issue 3 (10th December 2020) - Nagar, Anindyt; Myers, Sam; Kozareva, Diana; Simcoe, Mark; Hammond, Christopher
Abstract : Background/aims: Cascade screening has been used successfully in relatives of patients with inherited cancers and other genetic diseases to identify presymptomatic disease. This study was designed to examine if this approach would be successful in a high-risk group: first-degree relatives (FDR) of African-Caribbean glaucoma patients resident in London. Methods: African-Caribbean patients (probands) with glaucoma from an inner London hospital setting in a deprived area were asked to disseminate personalised information to their FDR over the age of 30 and to arrange a free hospital-based screening. Data collected, including optical coherence tomography imaging, were reviewed by a glaucoma specialist and if glaucoma was diagnosed or suspected, local specialist referral via family doctor was made. Results: 203 probands were recruited from glaucoma clinics. 248 suitable FDR were identified as potentially eligible to attend screening. 57 (23%) FDR made contact with the research team of whom 18 (7%) attended a subsequent screening visit. No patients were diagnosed with glaucoma; one participant was diagnosed as glaucoma suspect. Reasons for poor uptake included reluctance by probands to involve their family members, and retirees spending significant time abroad. Conclusion: Cascade screening of FDR of African-Caribbean glaucoma patients in inner city London was unsuccessful. Research confidentiality guidance prohibiting research teams directly contacting family members was a barrier. Greater community engagement, community-based screening and permission to contact FDR directly might have improved uptake.